Election of Indonesian Presidential Candidates: A Sociological Review - Riyono, Bado (International Journal of Law Analytics, 2023)
The presidential election is a competition for power in a constitutional manner. Elections every 5 years are a hope for better. The public chose to hope that the president could improve the situation for the better. This research uses qualitative methods with a sociological approach. Respondents were 6 candidates for election in 2024. The research results show that people tend to vote based on options that can increase their confidence through the issues presented by the candidate. It can be based on ethnicity, religion, friends or other things that can inspire voter confidence.